(untitled) (Asian Journal of Medical and Biological Research, 2018)
This study was carried out to investigate the drug resistance pattern of Salmonella spp. from diarrheal patients of under 5 years of age. Collected stool samples from the hospitalized diarrheal patients were analyzed for the presence of Salmonella spp. Among 350 stool samples from diarrheal patients, 15 (4%) were positive for the Salmonella spp. Antibiotic susceptibility test of the identified Salmonella spp. was performed according to Kirby-Bauer disc diffusion method. Eight commonly used antibiotics including azithromycin (15 μg), chloramphenicol (30 μg), Sulphamethaxole-trimethoprim (25 μg), metronidazole (50 μg), tetracycline (30 μg), doxycycline (30 μg), erythromycin (15 μg) and ciprofloxacin (5 μg) used to determine drug resistance pattern of the identified Salmonella spp. Majority of the isolates were multidrug resistant showed resistance against more than three drugs. 73% of Salmonella spp. was resistant to 2-4 drugs and 20% showed resistance to more than 5 drugs. We found that 100% Salmonella showed resistance to metronidazole and 87% were resistant to erythromycin. 7% isolates were resistant to chloramphenicol and doxycycline and 20% were resistant to ciprofloxacin. Antibiotic resistance is a serious public health problem worldwide and a leading cause of mortality and morbidity. This kind of situation, leads to great socioeconomic losses from the perspective of the patient, the hospital, and the whole society. To get rid form the drug resistance problem unnecessary, over and misuse of antibiotics should immediately prohibited and policy of judicious use of antibiotics should be strengthened. Asian J. Med. Biol. Res. December 2017, 3(4): 534-538